NiO-loaded P-doped porous NiSO4 composite structure nanosheet as well as preparation method and application thereof

The preparation of NiO-loaded P-doped porous NiSO4 composite nanosheets through electrochemical peeling and high-temperature calcination, which solves the problems of high working temperature and long response time of the sensing material, and achieves rapid response and high selectivity to H2S gas.

CN119873902AInactive Publication Date: 2025-04-25北京云摩科技股份有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097119.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing gas sensing materials have problems with high operating temperature, complex preparation processes and long response times, and cannot achieve fast and real-time detection of harmful gases.

Method used

Electrochemical peeling method was used to prepare NiO-loaded P-doped porous NiSO4 composite structure nanosheets, and heterojunction materials were formed through the synthesis of Ni(OH)2/NiPS3 precursor and high-temperature calcination, and the morphology and size of NiO were regulated to improve gas-sensitive sensing performance.

Benefits of technology

It realizes ppm-level response to H2S gas at an optimal operating temperature of 100°C, with a short response time (less than 20 s) and a reply time less than 10 s, with excellent gas sensing performance and gas selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873902A_ABST
    Figure CN119873902A_ABST
Patent Text Reader

Abstract

The invention provides a NiO-loaded P-doped porous NiSO4 composite structure nanosheet as well as a preparation method and application thereof.According to the NiO-loaded P-doped porous NiSO4 composite structure nanosheet, a 2D nanosheet with a rough local part and a rough edge is used as a substrate, and mesopores and lattice stripes exist on the surface; the lattice fringe intervals are measured to be 0.209 nm, 70.431 nm and 0.200 nm respectively, and the lattice fringe intervals are matched with the crystal face of NiO and the crystal face of NiSO4 respectively. According to the NiO-loaded P-doped porous NiSO4 composite structure nanosheet as well as the preparation method and the application thereof, the NiPS3 nanosheet is efficiently and quickly stripped through electrochemistry, a high-quality sheet structure can be prepared on a large scale within a short time, and a good substrate and a platform are provided for growth of NiO; the synthesis repeatability of the Ni (OH) 2 / NiPS3 precursor is high, and the steps are simple and easy to operate; and the morphology and size of NiO and the phase of the substrate can be regulated and controlled by controlling the annealing temperature, the grain size is prevented from being too large or the nanosheet structure is prevented from collapsing in the regulation and control process, and finally the heterojunction material loaded with NiO nanoparticles is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation, and in particular to a NiO-loaded P-doped porous NiSO4 composite structure nanosheet, a preparation method and an application thereof. Background Art

[0002] The continuous progress of social science and technology has promoted the rapid development of industry, but it has also led to the emission of a large amount of polluting gases, seriously affecting the atmospheric environment and threatening human survival and health.

[0003] Therefore, monitoring harmful gases has become a key link in controlling emissions and improving air quality. Among them, hydrogen sulfide (H2S), as a typical toxic gas, has attracted widespread attention in recent years, especially in terms of how to detect its concentration content in real time. In order to meet this demand, it is particularly important to develop gas sensors with low research and development costs and excellent performance. At present, many gas sensing materials face problems such as high operating temperature, complex preparation process and long response time, and cannot achieve rapid real-time detection.

[0004] Therefore, it is necessary to provide NiO-loaded P-doped porous NiSO4 composite structure nanosheets and preparation methods and applications to solve the above technical problems. Summary of the invention

[0005] The present invention provides a NiO-loaded P-doped porous NiSO4 composite structure nanosheet, a preparation method and an application thereof, which solve the problems of low sensing performance and high operating temperature. In order to solve the above technical problems, the present invention provides a NiO-loaded P-doped porous NiSO4 composite structure nanosheet, which is based on a 2D nanosheet with rough local and edge flakes, and has mesopores and lattice fringes on the surface; The lattice fringe spacings were measured to be 0.209 nm, 70.431 nm, and 0.200 nm, respectively, and coincide with the crystal planes of NiO and NiSO4, respectively.

[0006] To solve the above problems, the present invention also provides a method for preparing NiO-loaded P-doped porous NiSO4 composite structure nanosheets, comprising the following steps: S1. Electrochemical exfoliation of NiPS3 nanosheets: Bulk NiPS3 was exfoliated by electrochemical cathode exfoliation. Bulk NiPS3 crystals were sandwiched between metal platinum meshes, and the platinum mesh was sandwiched between platinum clips as working electrodes. Platinum wire electrodes were used as counter electrodes. 0.05 M tetrabutylammonium tetrafluoroborate (TBAB) was dissolved in N, N-dimethylformamide (DMF) solution (30 ml) as electrolyte. Electrochemical exfoliation of bulk NiPS3 crystals was completed using an electrochemical workstation. A static bias of −5 V was applied to the working electrode for a reaction time of 6 h. During the electrochemical exfoliation process, a large amount of NiPS3 crystals expanded and exfoliated to form a brown suspension. Subsequently, the suspension was collected and subjected to mild ice bath ultrasound for 90 min. The obtained product was thoroughly washed with anhydrous ethanol, centrifuged 5 times (10,000 rpm), precipitated, and dried at 60 °C under vacuum for 10 h. S2. Synthesis of Ni(OH)2 / NiPS3 precursor: 50 mg of two-dimensional NiPS3 nanosheets were ultrasonically dispersed in solution A; solution B was poured into solution A; stirred at room temperature for 1 hour; then the mixed solution was transferred to a 50 ml Teflon autoclave and heated at 140 °C for 8 h; Ni(OH)2 / NiPS3 nanosheets were collected by centrifugation, washed three times with ethanol, and finally dried under vacuum at 60 °C for 10 hours; S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; S4. Gas sensitivity test: To test the gas sensitivity of the material, the sensor element must be prepared first. The synthesized sensor material is evenly dispersed in ethanol by ultrasound to prepare a 20 mg / mL solution. The above solution is then dropped onto a commercial Au sensing electrode (2 μL) by a pipette. After the alcohol evaporates, a sensing layer is formed. The completed sensor element is placed in the test chamber, and the gas to be tested in the gas cylinder is opened. In the experiment, the gas flow is controlled by an MFC device (mass flow controller). At the same time, the air and target gas flow rates are adjusted to mix to prepare H2S concentrations at different concentrations. The mixed gas passes through the sensing material, and the resistance change data obtained will be displayed on the computer. The resistance change reflects the sensitivity to the target gas. The temperature control of the sensor is carried out by bringing the DC power supply into contact with the micro heater of the electrode substrate. The DC power supply is brought into contact with the micro heater of the electrode substrate, and the working temperature is adjusted by changing the output current value of the DC power supply to compare the sensing performance.

[0007] Preferably, the solution A is formed by dissolving Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of methanol (MeOH), and the solution B is formed by dissolving 2-methylimidazole (2-MeIm; 328.4 mg, 4 mmol) in 20 ml of MeOH.

[0008] Preferably, the reaction temperature in S3 is 350°C-750°C, and the reaction time is 4 hours.

[0009] Preferably, during the measurement process of S4, data is automatically collected through a Keithley2600b acquisition system.

[0010] Preferably, the horse boiling furnace used in S3 includes a horse boiling furnace body, a sliding cavity is opened inside the bottom of the horse boiling furnace body, a sliding groove is opened on the top of the sliding cavity, a driving motor is fixedly installed on the back of the horse boiling furnace body, a screw rod is fixedly installed on the output end of the driving motor, the outer side surface of the screw rod is threadedly connected to a limiting frame, a limiting groove is opened on the top of the limiting frame, a limiting block is clamped on the inner side of the limiting groove, and a placing plate is fixedly installed on the top of the limiting block.

[0011] Preferably, the limiting frame is slidably connected to the inner side surface of the sliding groove.

[0012] Preferably, a control switch is fixedly mounted on the side of the horse furnace body, and the control switch is electrically connected to the drive motor.

[0013] Preferably, a plurality of placement grooves are provided on the top of the placement plate.

[0014] In order to solve the above problems, the present invention also provides an application of a NiO-loaded P-doped porous NiSO4 composite structure nanosheet in the field of gas sensing.

[0015] Compared with the related art, the NiO-loaded P-doped porous NiSO4 composite structure nanosheets, preparation method and application provided by the present invention have the following beneficial effects: The present invention provides a NiO-loaded P-doped porous NiSO4 composite structure nanosheet, a preparation method and an application thereof. The electrochemical exfoliation of NiPS3 nanosheets is efficient and rapid, and high-quality sheet structures can be prepared on a large scale in a short time, providing a good substrate and platform for the growth of NiO. The synthesis of the Ni(OH)2 / NiPS3 precursor has high repeatability, and the steps are simple and easy to operate. The control of the subsequent annealing temperature can regulate the morphology and size of NiO, as well as the physical phase of the substrate, and prevent the grain size from being too large or the nanosheet structure from collapsing during the regulation process, thereby finally forming a heterojunction material loaded with NiO nanoparticles. For the NiO-loaded P-doped porous NiSO4 composite structure (NiO / NiSO4), NiO and P-doped NiSO4 carriers can play a synergistic role so that the composite material exhibits excellent gas-sensitive sensing performance, and the formed NiO nanoparticles have a high specific surface area and can provide high active sites. The presence of the heterojunction is conducive to providing higher carrier migration and enhancing the sensing performance. The preparation process is simple and the production cost is low. The NiO / NiSO4 heterojunction of the present invention can detect H2S as a gas-sensitive sensing material, and can achieve a ppm-level response to H2S gas at an optimal working temperature of 100°C, with a short response time (less than 20 s) and a recovery time of less than 10 s, which indicates that the NiO / NiSO4 heterojunction of the present invention has excellent gas sensing performance and has great application potential in the field of gas sensing; in addition, the NiO / NiSO4 sensor has excellent gas selectivity. At 100°C, compared with the sensor's poor gas-sensitive performance to 5 ppm NH3 and CO, the sensor's response value to H2S can reach more than 30 times. The sensor also has good working stability for five weeks. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Scanning electron microscope (SEM) images of (a) bulk NiPS3 and (b) electrochemically exfoliated NiPS3 nanosheets prepared in Example 1; Figure 2 This is the SEM image of the Ni(OH)2 / NiPS3 nanosheets prepared in Example 1; Figure 3 This is a SEM image of the NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 4 This is a transmission electron microscope (TEM) image of the NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 5 (a) High-resolution transmission electron microscopy (HR-TEM) image and (b) selected area electron diffraction image of NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 6XRD characterization of various heterostructures prepared in Examples 1 to 5; Figure 7 The gas sensing performance test of NiO / NiSO4 prepared in Example 1 at different temperatures; Figure 8 Concentration-response curves of NiO / NiSO4 prepared in Example 1 and other comparative samples; Fig. 9 Performance test of NiO / NiSO4 prepared in Example 1 at 100°C; Fig.10 A schematic diagram of the structure of a Maboise furnace used in the method for preparing a NiO-loaded P-doped porous NiSO4 composite structure provided by the present invention; Fig.11 for Fig.10 The schematic diagram of the cross-section structure shown; Fig.12 for Fig.11 The schematic diagram of the limiting frame structure from a top view is shown.

[0017] Numbers in the figure: 1. Horse furnace body, 11. Rubber pad, 2. Sliding cavity, 21. Sliding groove, 3. Driving motor, 31. Screw rod, 32. Limiting frame, 33. Limiting groove, 34. Limiting block, 35. Placing plate, 36. Placing groove, 4. Control switch. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.

[0019] Example 1 Please refer to Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 , Fig.11 and Fig.12 ,in, Figure 1 Scanning electron microscope (SEM) images of (a) bulk NiPS3 and (b) electrochemically exfoliated NiPS3 nanosheets prepared in Example 1; Figure 2 This is the SEM image of the Ni(OH)2 / NiPS3 nanosheets prepared in Example 1; Figure 3 This is a SEM image of the NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 4 This is a transmission electron microscope (TEM) image of the NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 5(a) High-resolution transmission electron microscopy (HR-TEM) image and (b) selected area electron diffraction image of NiO / Ni2SO4 nanosheets prepared in Example 1; Figure 6 XRD characterization of various heterostructures prepared in Examples 1 to 5; Figure 7 The gas sensing performance test of NiO / NiSO4 prepared in Example 1 at different temperatures; Figure 8 Concentration-response curves of NiO / NiSO4 prepared in Example 1 and other comparative samples; Fig. 9 Performance test of NiO / NiSO4 prepared in Example 1 at 100°C; Fig.10 A schematic diagram of the structure of a Maboise furnace used in the method for preparing a NiO-loaded P-doped porous NiSO4 composite structure provided by the present invention; Fig.11 for Fig.10 The schematic diagram of the cross-section structure shown; Fig.12 for Fig.11 A schematic diagram of the top view of the limiting frame shown. A NiO-loaded P-doped porous NiSO4 composite structure nanosheet, the material is based on a 2D nanosheet with rough local and edge flakes, and has mesopores and lattice fringes on the surface; The lattice fringe spacings were measured to be 0.209 nm, 70.431 nm, and 0.200 nm, respectively, and coincide with the crystal planes of NiO and NiSO4, respectively.

[0020] To solve the above problems, the present invention also provides a method for preparing NiO-loaded P-doped porous NiSO4 composite structure nanosheets, comprising the following steps: S1. Electrochemical exfoliation of NiPS3 nanosheets: Bulk NiPS3 was exfoliated by electrochemical cathode exfoliation. Bulk NiPS3 crystals were sandwiched between metal platinum meshes, and the platinum mesh was sandwiched between platinum clips as working electrodes. Platinum wire electrodes were used as counter electrodes. 0.05 M tetrabutylammonium tetrafluoroborate (TBAB) was dissolved in N, N-dimethylformamide (DMF) solution (30 ml) as electrolyte. Electrochemical exfoliation of bulk NiPS3 crystals was completed using an electrochemical workstation. A static bias of −5 V was applied to the working electrode for a reaction time of 6 h. During the electrochemical exfoliation process, a large amount of NiPS3 crystals expanded and exfoliated to form a brown suspension. Subsequently, the suspension was collected and subjected to mild ice bath ultrasound for 90 min. The obtained product was thoroughly washed with anhydrous ethanol, centrifuged 5 times (10,000 rpm), precipitated, and dried at 60 °C under vacuum for 10 h. S2. Synthesis of Ni(OH)2 / NiPS3 precursor: 50 mg of two-dimensional NiPS3 nanosheets were ultrasonically dispersed in solution A; solution B was poured into solution A; stirred at room temperature for 1 hour; then the mixed solution was transferred to a 50 ml Teflon autoclave and heated at 140 °C for 8 h; Ni(OH)2 / NiPS3 nanosheets were collected by centrifugation, washed three times with ethanol, and finally dried under vacuum at 60 °C for 10 hours; S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; S4. Gas sensitivity test: To test the gas sensitivity of the material, the sensor element must be prepared first. The synthesized sensor material is evenly dispersed in ethanol by ultrasound to prepare a 20 mg / mL solution. The above solution is then dropped onto a commercial Au sensing electrode (2 μL) by a pipette. After the alcohol evaporates, a sensing layer is formed. The completed sensor element is placed in the test chamber, and the gas to be tested in the gas cylinder is opened. In the experiment, the gas flow is controlled by an MFC device (mass flow controller). At the same time, the air and target gas flow rates are adjusted to mix to prepare H2S concentrations at different concentrations. The mixed gas passes through the sensing material, and the resistance change data obtained will be displayed on the computer. The resistance change reflects the sensitivity to the target gas. The temperature control of the sensor is carried out by bringing the DC power supply into contact with the micro heater of the electrode substrate. The DC power supply is brought into contact with the micro heater of the electrode substrate, and the working temperature is adjusted by changing the output current value of the DC power supply to compare the sensing performance.

[0021] The solution A was formed by dissolving Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of methanol (MeOH), and the solution B was formed by dissolving 2-methylimidazole (2-MeIm; 328.4 mg, 4 mmol) in 20 ml of MeOH.

[0022] The reaction temperature in S3 is 350°C-750°C, and the reaction time is 4 hours.

[0023] During the measurement of S4, data is automatically collected by a Keithley 2600b acquisition system.

[0024] The horse boiling furnace used in the S3 includes a horse boiling furnace body 1, a sliding cavity 2 is opened inside the bottom of the horse boiling furnace body, a sliding groove 21 is opened on the top of the sliding cavity 2, a driving motor 3 is fixedly installed on the back of the horse boiling furnace body 1, a screw rod 31 is fixedly installed on the output end of the driving motor 3, the outer side surface of the screw rod 31 is threadedly connected to a limiting frame 32, a limiting groove 33 is opened on the top of the limiting frame 32, the inner side surface of the limiting groove 33 is clamped with a limiting block 34, and a placement plate 35 is fixedly installed on the top of the limiting block 34.

[0025] The limiting frame 32 is slidably connected to the inner side surface of the sliding groove 21 .

[0026] A control switch 4 is fixedly mounted on the side of the horse furnace body 1 , and the control switch 4 is electrically connected to the drive motor 3 .

[0027] A plurality of placement grooves 36 are formed on the top of the placement plate 35 .

[0028] In order to solve the above problems, the present invention also provides an application of a NiO-loaded P-doped porous NiSO4 composite structure nanosheet in the field of gas sensing.

[0029] Compared with the related art, the NiO-loaded P-doped porous NiSO4 composite structure nanosheets, preparation method and application provided by the present invention have the following beneficial effects: Electrochemical exfoliation of NiPS3 nanosheets is efficient and rapid, and high-quality sheet structures can be prepared on a large scale in a short time, providing a good substrate and platform for the growth of NiO. The synthesis of the Ni(OH)2 / NiPS3 precursor is highly reproducible, and the steps are simple and easy to operate. The subsequent annealing temperature control can regulate the morphology and size of NiO, as well as the physical phase of the substrate, and prevent the grain size from being too large or the nanosheet structure from collapsing during the regulation process, ultimately forming a heterojunction material loaded with NiO nanoparticles. For the NiO-loaded P-doped porous NiSO4 composite structure (NiO / NiSO4), NiO and P-doped NiSO4 carriers can play a synergistic role in making the composite material exhibit excellent gas-sensitive sensing performance. The formed NiO nanoparticles have a high specific surface area and can provide high active sites. The presence of the heterojunction is conducive to providing higher carrier migration and enhancing the sensing performance. The preparation process is simple and the production cost is low. The NiO / NiSO4 heterojunction of the present invention can detect H2S as a gas-sensitive sensing material, and can achieve a ppm-level response to H2S gas at an optimal working temperature of 100°C, with a short response time (less than 20 s) and a recovery time of less than 10 s, which indicates that the NiO / NiSO4 heterojunction of the present invention has excellent gas sensing performance and has great application potential in the field of gas sensing; in addition, the NiO / NiSO4 sensor has excellent gas selectivity. At 100°C, compared with the sensor's poor gas-sensitive performance to 5 ppm NH3 and CO, the sensor's response value to H2S can reach more than 30 times. The sensor also has good working stability for five weeks.

[0030] Example 2 S1. Electrochemical exfoliation of NiPS3 nanosheets: NiPS3 bulk crystals were sandwiched in a metal platinum mesh and fixed on the platinum clip as the working electrode, while a platinum wire electrode was used as the counter electrode; 30 ml of DMF solution dissolved with 0.05 M TBAB was prepared as the electrolyte; NiPS3 crystals were exfoliated on an electrochemical workstation with a static bias of −5 V applied for 6 hours; then, the suspension was collected and subjected to mild ice bath sonication for 90 minutes; finally, the product was thoroughly washed with anhydrous ethanol and centrifuged 5 times (10,000 rpm) to obtain a precipitate, which was then vacuum dried at 60 °C for 10 hours; S2. Synthesis of Ni(OH)2 / NiPS3 precursor: Dissolve Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of MeOH to obtain solution A. Meanwhile, dissolve 2-MeIm (328.4 mg, 4 mmol) in 20 ml of MeOH to form solution B. Then, ultrasonically disperse 50 mg of two-dimensional NiPS3 nanosheets in solution A, and then add solution B to solution A. Stir at room temperature for 1 hour. After that, transfer the mixed liquid to a 50 ml Teflon autoclave and heat at 140 °C for 8 hours. Finally, collect Ni(OH)2 / NiPS3 nanosheets by centrifugation, wash three times with ethanol, and dry under vacuum at 60 °C for 10 hours. S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; the reaction temperature is 550°C and the reaction time is 4 h.

[0031] Example 3 S1. Electrochemical exfoliation of NiPS3 nanosheets: NiPS3 bulk crystals were sandwiched in a metal platinum mesh and fixed on the platinum clip as the working electrode, while a platinum wire electrode was used as the counter electrode; 30 ml of DMF solution dissolved with 0.05 M TBAB was prepared as the electrolyte; NiPS3 crystals were exfoliated on an electrochemical workstation with a static bias of −5 V applied for 6 hours; then, the suspension was collected and subjected to mild ice bath sonication for 90 minutes; finally, the product was thoroughly washed with anhydrous ethanol and centrifuged 5 times (10,000 rpm) to obtain a precipitate, which was then vacuum dried at 60 °C for 10 hours; S2. Synthesis of Ni(OH)2 / NiPS3 precursor: Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) was dissolved in 20 ml of MeOH to obtain solution A. At the same time, 2-MeIm (328.4 mg, 4 mmol) was also dissolved in 20 ml of MeOH to form solution B. Next, 50 mg of two-dimensional NiPS3 nanosheets were ultrasonically dispersed in solution A, and then solution B was added to solution A. Stir at room temperature for 1 hour. After that, the mixed liquid was transferred to a 50 ml Teflon autoclave and heated at 140 °C for 8 hours. Finally, the Ni(OH)2 / NiPS3 nanosheets were collected by centrifugation, washed three times with ethanol, and dried under vacuum conditions at 60 °C for 10 hours.

[0032] S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; the reaction temperature is 350°C and the reaction time is 4 h.

[0033] Example 4 S1. Electrochemical exfoliation of NiPS3 nanosheets: NiPS3 bulk crystals were sandwiched in a metal platinum mesh and fixed on the platinum clip as the working electrode, while a platinum wire electrode was used as the counter electrode; 30 ml of DMF solution dissolved with 0.05 M TBAB was prepared as the electrolyte; NiPS3 crystals were exfoliated on an electrochemical workstation with a static bias of −5 V applied for 6 hours; then, the suspension was collected and subjected to mild ice bath sonication for 90 minutes; finally, the product was thoroughly washed with anhydrous ethanol and centrifuged 5 times (10,000 rpm) to obtain a precipitate, which was then vacuum dried at 60 °C for 10 hours; S2. Synthesis of Ni(OH)2 / NiPS3 precursor: Dissolve Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of MeOH to obtain solution A. Meanwhile, dissolve 2-MeIm (328.4 mg, 4 mmol) in 20 ml of MeOH to form solution B. Then, ultrasonically disperse 50 mg of two-dimensional NiPS3 nanosheets in solution A, and then add solution B to solution A. Stir at room temperature for 1 hour. After that, transfer the mixed liquid to a 50 ml Teflon autoclave and heat at 140 °C for 8 hours. Finally, collect Ni(OH)2 / NiPS3 nanosheets by centrifugation, wash three times with ethanol, and dry under vacuum at 60 °C for 10 hours. S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor was placed in a muffle furnace in air for high-temperature calcination at a reaction temperature of 450°C and a reaction time of 4 h.

[0034] Example 5 S1. Electrochemical exfoliation of NiPS3 nanosheets: NiPS3 bulk crystals were sandwiched in a metal platinum mesh and fixed on the platinum clip as the working electrode, while a platinum wire electrode was used as the counter electrode; 30 ml of DMF solution dissolved with 0.05 M TBAB was prepared as the electrolyte; NiPS3 crystals were exfoliated on an electrochemical workstation with a static bias of −5 V applied for 6 hours; then, the suspension was collected and subjected to mild ice bath sonication for 90 minutes; finally, the product was thoroughly washed with anhydrous ethanol and centrifuged 5 times (10,000 rpm) to obtain a precipitate, which was then vacuum dried at 60 °C for 10 hours; S2. Synthesis of Ni(OH)2 / NiPS3 precursor: Dissolve Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of MeOH to obtain solution A. Meanwhile, dissolve 2-MeIm (328.4 mg, 4 mmol) in 20 ml of MeOH to form solution B. Then, ultrasonically disperse 50 mg of two-dimensional NiPS3 nanosheets in solution A, and then add solution B to solution A. Stir at room temperature for 1 hour. After that, transfer the mixed liquid to a 50 ml Teflon autoclave and heat at 140 °C for 8 hours. Finally, collect Ni(OH)2 / NiPS3 nanosheets by centrifugation, wash three times with ethanol, and dry under vacuum at 60 °C for 10 hours. S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; the reaction temperature is 650°C and the reaction time is 4 h.

[0035] Example 6 S1. Electrochemical exfoliation of NiPS3 nanosheets: NiPS3 bulk crystals were sandwiched in a metal platinum mesh and fixed on the platinum clip as the working electrode, while a platinum wire electrode was used as the counter electrode; 30 ml of DMF solution dissolved with 0.05 M TBAB was prepared as the electrolyte; NiPS3 crystals were exfoliated on an electrochemical workstation with a static bias of −5 V applied for 6 hours; then, the suspension was collected and subjected to mild ice bath sonication for 90 minutes; finally, the product was thoroughly washed with anhydrous ethanol and centrifuged 5 times (10,000 rpm) to obtain a precipitate, which was then vacuum dried at 60 °C for 10 hours; S2. Synthesis of Ni(OH)2 / NiPS3 precursor: Dissolve Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of MeOH to obtain solution A. Meanwhile, dissolve 2-MeIm (328.4 mg, 4 mmol) in 20 ml of MeOH to form solution B. Then, ultrasonically disperse 50 mg of two-dimensional NiPS3 nanosheets in solution A, and then add solution B to solution A. Stir at room temperature for 1 hour. After that, transfer the mixed liquid to a 50 ml Teflon autoclave and heat at 140 °C for 8 hours. Finally, collect Ni(OH)2 / NiPS3 nanosheets by centrifugation, wash three times with ethanol, and dry under vacuum at 60 °C for 10 hours. S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; the reaction temperature is 750°C and the reaction time is 4 h.

[0036] The samples prepared in Examples 1-5 were characterized and tested, and the results were as follows: See also Figure 1 , Figure 1 Scanning electron microscope (SEM) images of (a) bulk NiPS3 and (b) electrochemically exfoliated NiPS3 nanosheets prepared in Example 1. Bulk NiPS3 is a typical layered structure. Through a simple electrochemical exfoliation method, bulk NiPS3 can expand and be exfoliated into thinner NiPS3 nanosheets under the action of ultrasound.

[0037] See also Figure 2, SEM image of Ni(OH)2 / NiPS3 nanosheets prepared in Example 1. After hydrothermal treatment, the morphology of the 2D NiPS3 nanosheets did not change significantly, and the sheet structure was still maintained, which was conducive to the exposure of the active surface. In the formed Ni(OH)2 / NiPS3 precursor, granular substances were dispersed on the 2D NiPS3 nanosheets, and it was observed that they were very uniform in size. This island-like distribution and the anchoring effect of the matrix will produce a coupling effect on the upper particles and the nanosheet matrix, leading to the optimization of the structure-activity relationship.

[0038] See also Figure 3 , Figure 3 This is the SEM image of the NiO / Ni2SO4 nanosheets prepared in Example 1. After the Ni(OH)2 / NiPS3 precursor was annealed at 550℃ for 4 h, the morphology of the product changed. The 2D nanosheet base was no longer smooth and flat, and its local area and edges became rough. It can be inferred that its structural phase has changed significantly. In addition, the upper nanoparticles are no longer distributed on the collective surface in a smooth granular state, but have a clear tendency to embed into the matrix surface and gradually merge with the matrix.

[0039] See also Figure 4 , Figure 4 This is a transmission electron microscope (TEM) image of the NiO / Ni2SO4 nanosheets prepared in Example 1. It can be observed that there are mesopores on the nanosheets loaded with particles.

[0040] See also Figure 5 , Figure 5 (a) High-resolution transmission electron microscopy (HR-TEM) image and (b) selected area electron diffraction image of NiO / Ni2SO4 nanosheets prepared in Example 1. The lattice fringes shown in the HRTEM image have interplanar spacings measured to be 0.209nm, 70.431nm, and 0.200nm, respectively, which coincide with the (200) crystal plane of NiO, and the (110) and (202) crystal planes of NiSO4, respectively. The interface between NiO and NiSO4 is clearly visible, proving the heterogeneous coupling between the two. Figure (b) is the SAED image of the Ni(OH)2 / NiPS3 550℃ annealing product, and its sharp diffraction spots correspond to the (111), (200), and (220) crystal planes of NiO, and the (112) and (202) crystal planes of NiSO4, respectively.

[0041] See also Figure 6 , Figure 6XRD characterization of various heterostructures prepared in Examples 1-5; standard PDF cards of various materials are also given in the figure. The XRD diffraction peak positions of the samples annealed at 350℃ and 450℃ are similar, which are consistent with the (001), (002), (130), (131), (-133) and (-331) crystal planes in the standard JCPDF card (01-078-0499) of NiPS3 and the (100), (101) and (102) crystal planes in the standard JCPDF card (00-002-1280) of NiS. This may be caused by the gradual oxidation and dehydrogenation of nickel hydroxide in the sample and the oxidation of the substrate, which causes phosphorus to be redistributed in the newly generated sulfide in the form of a doping state. Similarly, the XRD diffraction peak positions of the samples annealed at 550℃ and 650℃ are similar, but have changed significantly compared with the samples annealed at 350℃ and 450℃. It is consistent with the (110), (020), (111), (021), (112), (130), (202), (222), (042), (004) and (242) crystal planes in the standard JCPDF card (00-004-0835) of NiSO4 and the (111), (200), (220) and (311) crystal planes in the standard JCPDF card (00-004-0835) of NiO. When the temperature is raised to 750℃, the phase of the sample becomes more complex, which is consistent with the (110), (020), (111), (021), (200), (112), (130), (202) and (222) crystal planes in the standard JCPDF card (00-013-0435) of NiSO4, the (111), (200), (220) and (311) crystal planes in the standard JCPDF card (00-004-0835) of NiO, and the (111), (12-1), (130) and (031) crystal planes in the standard JCPDF card (00-033-0950) of Ni2P2O7. The formation of more types of oxides also proves the complete destruction and disintegration of the base NiPS3 crystal structure.

[0042] See also Figure 7 , Figure 7The gas sensing performance test of NiO / NiSO4 prepared in Example 1 at different temperatures. (a) Response-recovery curve at different temperatures, (b) sensitivity comparison at different temperatures, (c) response / recovery time comparison at different temperatures. It can be seen from Figure (a) that when the gas concentration is constant, as the temperature increases, the sensitivity of the NiO / NiSO4 sensor first increases and then decreases. Figure (b) compares the sensitivity at different temperatures. It can be seen that the sensitivity of the sensor is the highest at 100°C, which can reach about 40, so 100°C is the best response temperature. When the temperature is low, the active sites on the surface of the sensing material are not activated. At this time, the target gas molecules that can be adsorbed on the surface of the material are relatively small, resulting in a low response value. As the temperature increases, the sites on the surface of the sensing layer gradually increase, and the adsorbed gas molecules also increase accordingly, which is reflected in the greatly improved sensing response value. However, when the temperature exceeds the optimal temperature of the material, the rate of gas molecules adsorbed on the surface of the material is less than the rate of desorption from the surface, so the response value decreases instead. Figure (c) shows the response time and recovery time comparison at different temperatures. It can be seen that the response time and recovery time tend to decrease with increasing temperature. The samples at 100℃ and 200℃ show good response-recovery time. Considering the sensitivity and energy consumption, it is believed that 100℃ is the optimal operating temperature of NiO / NiSO4 sensor.

[0043] See also Figure 8 , Figure 8 The concentration-response curves of NiO / NiSO4 prepared in Example 1 and other comparative samples. (a) Response curve of d-NiO to 0.05-5 ppm H2S, (b) Response curve of NiO to 0.05-5 ppm H2S, (c) Response curve of NiO / NiSO4 to 0.05-5 ppm H2S, (d) H2S concentration-response curve. It can be seen from Figures (ac) that with the increase of gas concentration, the sensitivity of each sample continues to increase. Among them, NiO / NiSO4 has a higher sensitivity value than d-NiO and NiO. Their response-concentration curves are plotted in Figure (d). It can be seen from the figure that NiO / NiSO4 has the largest slope value and has the best sensitivity at each concentration, so NiO / NiSO4 has the best sensing performance.

[0044] See also Fig. 9 , Fig. 9Performance test of NiO / NiSO4 prepared in Example 1 at 100°C. (a) Response curve of NiO / NiSO4 to 5 ppm H2S, (b) long-term stability test for five weeks, (c) response performance test to different gases. As shown in Figure (a), the performance of NiO / NiSO4 has good reversibility. In addition, as shown in Figure (b), a stability test of up to five weeks was carried out, using the same test conditions, that is, the test concentration of 5 ppm H2S gas and the operating temperature of 100°C. During the test, it can be seen that the gas-sensitive response value fluctuates around 40, and the response value shows a downward trend as the number of days increases. Due to its long-term exposure, the gas-sensitive performance will decay, but it remains stable as a whole. For practical applications, the selectivity of the sensor should be regarded as another main parameter. Figure (c) shows the selectivity of the NiO / NiSO4 sensor to 5 ppm NH3, CO, and H2S+50%RH at 100°C. It can be seen that the sensor has a relatively small response to NH3 and CO gases, and has poor sensing characteristics, while the response value to H2S can reach more than 30 times. Obviously, compared with other test gases, the NiO / NiSO4 sensor has excellent H2S selectivity.

[0045] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A NiO-loaded P-doped porous NiSO4 composite structure nanosheet, characterized in that: The material is based on 2D nanosheets that are rough locally and at the edges and are in the form of flakes, and there are mesopores and lattice fringes on the surface; The lattice fringe spacings were measured to be 0.209 nm, 70.431 nm, and 0.200 nm, respectively, and coincide with the crystal planes of NiO and NiSO4, respectively.

2. A method for preparing the NiO-loaded P-doped porous NiSO4 composite structure nanosheets as claimed in claim 1, characterized in that: The following steps are involved: S1. Electrochemical exfoliation of NiPS3 nanosheets: Bulk NiPS3 was exfoliated by electrochemical cathode exfoliation. Bulk NiPS3 crystals were sandwiched between metal platinum meshes, and the platinum mesh was sandwiched between platinum clips as working electrodes. Platinum wire electrodes were used as counter electrodes. 0.05 M tetrabutylammonium tetrafluoroborate (TBAB) was dissolved in N, N-dimethylformamide (DMF) solution (30 ml) as electrolyte. Electrochemical exfoliation of bulk NiPS3 crystals was completed using an electrochemical workstation. A static bias of −5 V was applied to the working electrode for a reaction time of 6 h. During the electrochemical exfoliation process, a large amount of NiPS3 crystals expanded and exfoliated to form a brown suspension. Subsequently, the suspension was collected and subjected to mild ice bath sonication for 90 min. The obtained product was thoroughly washed with anhydrous ethanol, centrifuged 5 times (10,000 rpm), precipitated, and dried at 60 °C under vacuum for 10 h. S2. Synthesis of Ni(OH)2 / NiPS3 precursor: 50 mg of two-dimensional NiPS3 nanosheets were ultrasonically dispersed in solution A; solution B was poured into solution A; stirred at room temperature for 1 hour; then the mixed solution was transferred to a 50 ml Teflon autoclave and heated at 140 °C for 8 h; Ni(OH)2 / NiPS3 nanosheets were collected by centrifugation, washed three times with ethanol, and finally dried under vacuum at 60 °C for 10 hours; S3. Formation of heterostructure materials: The dried Ni(OH)2 / NiPS3 precursor is placed in a muffle furnace in air for high-temperature calcination; S4. Gas sensitivity test: To test the gas sensitivity of the material, the sensor element must be prepared first. The synthesized sensor material is evenly dispersed in ethanol by ultrasound to obtain a 20 mg / mL solution. The solution is then dropped onto a commercial Au sensing electrode (2 microliters) by a pipette. After the alcohol evaporates, a sensing layer is formed. The completed sensor element is placed in the test chamber, and the gas to be tested in the gas cylinder is opened. In the experiment, the gas flow is controlled by an MFC device (mass flow controller). At the same time, the air and target gas flow rates are adjusted to mix to prepare H2S concentrations at different concentrations. The mixed gas passes through the sensor material, and the resistance change data obtained will be displayed on the computer. The resistance change reflects the sensitivity to the target gas. The temperature control of the sensor is carried out by bringing the DC power supply into contact with the micro heater of the electrode substrate; the DC power supply is brought into contact with the micro heater of the electrode substrate, and the operating temperature is adjusted by changing the output current value of the DC power supply, thereby comparing the sensing performance.

3. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 2, characterized in that: The solution A was formed by dissolving Ni(NO3)2·6H2O (261.7 mg, 0.9 mmol) in 20 ml of methanol (MeOH), and the solution B was formed by dissolving 2-methylimidazole (2-MeIm; 328.4 mg, 4 mmol) in 20 ml of MeOH.

4. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 2, characterized in that: The reaction temperature in S3 is 350°C-750°C, and the reaction time is 4 hours.

5. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 2, characterized in that: During the measurement of S4, data is automatically collected by a Keithley 2600b acquisition system.

6. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 2, characterized in that: The horse boiling furnace used in the S3 includes a horse boiling furnace body, a sliding cavity is opened inside the bottom of the horse boiling furnace body, a sliding groove is opened on the top of the sliding cavity, a driving motor is fixedly installed on the back of the horse boiling furnace body, a screw rod is fixedly installed on the output end of the driving motor, the outer side surface of the screw rod is threadedly connected to a limiting frame, a limiting groove is opened on the top of the limiting frame, a limiting block is clamped on the inner side of the limiting groove, and a placing plate is fixedly installed on the top of the limiting block.

7. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 6, characterized in that: The limiting frame is slidably connected to the inner side surface of the sliding groove.

8. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 6, characterized in that: A control switch is fixedly installed on the side of the horse furnace body, and the control switch is electrically connected to the driving motor.

9. The method for preparing a NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 6, characterized in that: A plurality of placement grooves are arranged on the top of the placement plate.

10. Application of the NiO-loaded P-doped porous NiSO4 composite structure nanosheet according to claim 1 in the field of gas sensing.